Penerapan Metode Six Sigma Pada Pengendalian Kualitas Air Baku Pada Produksi Makanan - Dino Rimantho; Desak Made Mariani (Jurnal Ilmiah Teknik Industri, 2017)
The quality of water as a raw material in the process of food production has an important role. Water quality control is the key in maintaining production. This is the underlying purpose of this study to make improvements in its production activities to reduce the number of defective products in the production process. Water quality control of production is done by specifying several parameters, such as pH, turbidity, and iron. This study uses the concept of Six Sigma DMAIC.Pareto diagram shows water tends to acid, muddy, and contain much iron. Furthermore, the fishbone diagram is used to determine the percentage biggest defect. Improvement performed at the highest RPN value of around 630 in the filter. In addition, the value of sigma level before improvement around 3.3 with the possibility of defects approximately 34491 to a million process. Furthermore, the level of sigma after improvement roughly 4:09 with the possible failure of the process around 5526.